¿Cuál es el efecto del rol de las mujeres rurales sobre la adecuada cloración del agua? Evidencia para el caso peruano - Sotelo Tornero, Marisela (2023)
This research analyzes the relevance of the role of rural women in ensuring proper water chlorination, taking into account an evaluation at the national rural level, as well as the differences between the concentrated and dispersed population centers. Specifically, this study focuses its analysis on those population centers with under 2000 inhabitants that are supplied with water and sewerage services by a rural service provider known as a communal organization in Peru. Based on a review of the literature, it is suggested that the low female participation in these communal organizations is one of the factors contributing to the persistently low rate of water suitable for human consumption. To conduct this study, data were collected from the Diagnóstico sobre el abastecimiento de agua y saneamiento en el ámbito rural - DATASS 2020 of the Ministerio de Vivienda, Construcción y Saneamiento (MVCS) (2020). This report provides information about sanitation services in rural population centers. Furthermore, the hypotheses formulated in this study were validated in the Results section through probabilistic regression analysis, utilizing a water service quality index represented by proper chlorination.